An extension of Dragilev's theorem for the existence of periodic solutions of the Liénard equation. (November 2015) - Cioni, Martina; Villari, Gabriele
Abstract: The problem of the existence of periodic solution for the Liénard equation is investigated, and a result which improves the classical Dragilev's theorem is presented, together with a corollary in which there are no assumptions on the function g ( x ), and hence on G ( x ), besides the standard sign condition. In the final part of the paper constructive examples with several limit cycles are provided.